2022
DOI: 10.1002/lpor.202100393
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Reconfigurable Electromagnetically Induced Transparency with Terahertz Chalcogenide Metasurfaces

Abstract: Metasurface analog of electromagnetically induced transparency (EIT) provides a compact platform for generating a narrow-band transmission window with very sharp spectral features. They hold promise for many appealing applications including ultrasensitive detectors, slow-light devices, nonlinear optical devices etc. In particular, reconfigurable EIT metasurfaces are crucial for expanding the capability of light field control, which are promising for terahertz (THz) communications and optical networks. Yet, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…The slight discrepancy between the experiment and simulation was possibly caused by the presence of a rough surface and imperfect fabrication. [ 29 ] For the amorphous state (Figure 3c), it was revealed that such wideband and high‐efficiency performance was sustained over a broad θ i range from 0° to 75° with a step of 2°. The broadband operation stemmed from multiple peak polarization conversion superposition around 0.68, 1, and 1.48 THz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slight discrepancy between the experiment and simulation was possibly caused by the presence of a rough surface and imperfect fabrication. [ 29 ] For the amorphous state (Figure 3c), it was revealed that such wideband and high‐efficiency performance was sustained over a broad θ i range from 0° to 75° with a step of 2°. The broadband operation stemmed from multiple peak polarization conversion superposition around 0.68, 1, and 1.48 THz.…”
Section: Resultsmentioning
confidence: 99%
“…[26] Chalcogenide alloy (i.e., Ge-Sb-Te, GST) is a typical phase change material (PCM) possessing significantly different optical characteristics at the different crystallographic phases of amorphous and crystalline, [27] showing a talented candidate for obtaining the tunable metamaterials. [28,29] Nucleation dynamics drove the phase change of GST. [30] By continuously modulating the crystallization portion of GST, one can achieve the analog response instead of binary transition phases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metasurfaces, two-dimensional metamaterials constructed by planar meta-atoms with designable EM responses arranged in some specific global orders, have shown great capabilities to manipulate EM waves with many fascinating effects discovered [1][2][3] , including anomalous reflection/refraction [4][5][6] , meta-lensing [7][8][9] , polarization conversion [10][11][12][13] , meta-hologram [14][15][16][17] , surface-wave manipulations [18][19][20][21] , electromagnetically induced transparency [22] , and many others [23][24][25][26][27][28][29] . Since the metasurface is flat and ultra-thin, it forms an ideal platform to realize multifunctional EM devices.…”
Section: Introductionmentioning
confidence: 99%
“…Since there are few natural materials with specific electromagnetic responses in the THz band, metamaterials (MMs) composed of artificially designed subwavelength resonators offer great application prospects in the manipulation of electromagnetic waves [8][9][10]. The electromagnetic properties of MMs are determined not by their constitutive materials but by their periodic unit structures.…”
Section: Introductionmentioning
confidence: 99%